Association between perioperative continuous glucose monitoring and clinically relevant postoperative pancreatic fistula (CR-POPF) in pancreatic surgery: a protocol for a prospective cohort study - Yuguang Huang; Yuelun Zhang; Ling Lan; Yi Zhang; Le Zhang; Le Shen (BMJ Open)
Introduction Surgical resection is the cornerstone therapy for pancreatic neoplasms, particularly in cases of resectable pancreatic carcinoma identified in the early stages. Clinically relevant postoperative pancreatic fistula (CR-POPF) persists as a prevalent and formidable postsurgical complication, substantially elevating patient morbidity and mortality. The current literature reveals a gap in the understanding of the relationship between perioperative glucose levels and the incidence of CR-POPF in patients undergoing pancreatic surgery. This study aims to investigate the association between perioperative glycaemic levels, specifically monitoring both blood and interstitial fluid glucose levels via non-invasive continuous glucose monitoring (CGM) and the occurrence of CR-POPF.Methods and analysis This observational prospective cohort study will be conducted at high-volume general hospitals in China. Adult patients scheduled for elective pancreatic surgeries from 1 March 2024 to 31 March 2025 will be prospectively enrolled, and the end date of the whole study is 31 July 2025. Eligible patients will wear a CGM system before surgery, and real-time interstitial fluid blood glucose levels will be monitored up to 14 days after surgery, or until the patient is discharged from the hospital. Patient characteristics and perioperative data will be collected using a standard case report form. The primary outcome is the incidence of CR-POPF during the hospital stay. The secondary outcomes include other postoperative complications, such as bile leakage, chyle leak, postoperative haemorrhage, intra-abdominal infection, and delayed gastric emptying, and in-hospital mortality.Ethics and dissemination The study protocol was approved by the Research Ethics Committee of Peking Union Medical College Hospital (IRB K-2501). Written informed consent will be obtained from all participants before study enrolment. The results of this study will be disseminated at scientific conferences and published in international peer-reviewed journals.Trial registration number NCT06289530.